1992
DOI: 10.1111/j.1476-5381.1992.tb14403.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 17β‐oestradiol on contraction, Ca2+ current and intracellular free Ca2+ in guinea‐pig isolated cardiac myocytes

Abstract: 4 17P-Oestradiol (10 and 30 SM) decreased the peak inward Ca2+ current (ICa), which was sensitive to [Ca2+]0, dihydropyridines and isoprenaline, to 59 ± 3% and 39 + 5% (n = 7-9, P<0.01) respectively, without producing any significant change in the shape of the current-voltage relationship.5 The recovery time of ICa from inactivation was delayed by 17p-oestradiol (10 tiM). The inhibitory effect of 17p-oestradiol on ICa was less at a holding potential of -80 mV than at -40 mV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
122
1
4

Year Published

2000
2000
2007
2007

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 241 publications
(141 citation statements)
references
References 20 publications
(22 reference statements)
14
122
1
4
Order By: Relevance
“…The profound inhibition of I Ca,L by raloxifene over the range of potentials tested is similar to previously documented direct actions of 17b-oestradiol on cardiac myocytes (Jiang et al, 1992;Grohe et al, 1996;Nakajima et al, 1999a). However, raloxifene did not significantly shift the steady-state activation or inactivation curves.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The profound inhibition of I Ca,L by raloxifene over the range of potentials tested is similar to previously documented direct actions of 17b-oestradiol on cardiac myocytes (Jiang et al, 1992;Grohe et al, 1996;Nakajima et al, 1999a). However, raloxifene did not significantly shift the steady-state activation or inactivation curves.…”
Section: Discussionsupporting
confidence: 87%
“…Similar experiments on field stimulated myocytes were performed with 17b-oestradiol in order to compare the acute actions of the two oestrogenic compounds. As the acute cardiac actions of 17b-oestradiol have previously been demonstrated to occur at supra-physiological concentrations (Jiang et al, 1992;Meyer et al, 1998), we chose to use a concentration of 40 mM in these experiments. Both raloxifene and 17b-oestradiol significantly decreased cell shortening and the Dindo-1 ratio (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one concentration of drug or vehicle was tested per cell and myocytes from at least three rats were used to acquire data for each drug concentration. Concentrations of 10 and 30 mM were examined first, as these had been reported to be effective previously in guinea-pig myocytes (Jiang et al, 1992) then further concentrations were examined to explore the full concentration-response relationship.…”
Section: Methodsmentioning
confidence: 99%
“…In previous work on the action of 17b-estradiol on I CaL in cardiac myocytes, only cells from male guinea pigs were studied (Jiang et al, 1992) or the inhibition of the current was reported to be independent of sex (Meyer et al, 1998). However, Ca 2 þ entry into vascular smooth muscle cells was inhibited by 17b-estradiol to a much greater extent in cells from female rats than in those from male rats (Crews and Khalil, 1999).…”
Section: Concentrations Of 17b-estradiolmentioning
confidence: 99%